41 Malignant Pheochromocytoma With a Rare Metastasis to Thoracic Spine. (11th January 2018) - Reddy, Amit; Orr, Wayne; Kaur, Jaswinder; Manucha, Varsha
Abstract: Pheochromocytoma is a rare, destructive neuroendocrine malignancy that occurs primarily in the adrenal glands and can metastasize anywhere along the sympathetic chain. The diagnosis of malignant pheochromocytoma is often problematic to analyze microscopically and thus primarily dependent on the existence of local invasion or metastasis. The incidence of malignant pheochromocytoma is approximately 10% with bone metastases being most common. However, vertebral involvement is exceedingly rare with only a few cases reported. We present a case of malignant pheochromocytoma with metastatic lesions to the thoracic spine. A 60-year-old woman presented with a constant cough in the setting of increasingly intense headaches, dizziness, nausea, and vomiting over a few weeks. A chest x-ray revealed a nodule. Laboratory work-up showed significantly elevated catecholamines in both blood and urine. Computerized tomography (CT) scan demonstrated a large right sided adrenal mass with metastatic lesions to liver, sacrum and bilateral iliac bones. A radical right adrenalectomy was performed with tumor measuring 5.9x5.6cm extending into the peri-renal fat. Focal renal capsular invasion at superior pole and lymphovascular invasion was identified. Multiple wedge resections of liver and right nephrectomy were performed. Immunohistochemistry demonstrated tumor cells positive for synaptophysin and chromogranin; S100 focally highlighted sustentacular cells. Stains for cytokeratin, calretinin and MART-1 were negative. Ki-67 was approximately 8%-10%. Findings were consistent with pheochromocytoma. Germline genetic testing revealed no mutations. Patient complained of back pain at three-month follow-up. CT showed T11 and T12 thoracic spine lesions. Subsequent bone biopsy contained bony trabeculae with trilineage hematopoietic elements and interspersed tumor cells positive for synaptophysin and negative for leukocyte common antigen, consistent with a metastatic pheochromocytoma. She underwent radiofrequency ablation and cement augmentation to the thoracic spine lesions. The surgical, radiological, and pathological overlap of this case highlights the importance of a multidisciplinary approach to these patients.